Sound production by dusky grouper Epinephelus marginatus at spawning aggregation sites. Issue 2 (16th July 2015) - Bertucci, F.; Lejeune, P.; Payrot, J.; Parmentier, E.
<x xml:space="preserve">Abstract</x> Sound production by the dusky grouper Epinephelus marginatus was monitored both in captivity and at two Mediterranean spawning sites during the summers of 2012 and 2013. The results of long‐term passive acoustic recordings provide for the first time a description of the sounds produced by E. marginatus. Two types of sounds were mainly recorded and consisted of low‐frequency booms that can be produced singly or in series with dominant frequencies below 100 Hz. Recordings in captivity validated these sounds as belonging to E. marginatus and suggested that they may be associated with reproductive displays usually performed during early stages of courtship behaviour. This study also allowed the identification of a third, low‐frequency growl‐like type of sound typically found in other grouper species. These growls were, however, not recorded in tanks and it is cautiously proposed that they are produced by E. marginatus. Acoustic signals attributed to E. marginatus were produced throughout the spawning season, with a diel pattern showing an increase before dusk, i.e. from 1900 to 2200 hours, before decreasing until the morning. The occurrence of sounds during the spawning season of this species suggests that they are probably involved in social activity occurring close to aggregation sites. Passive acoustics offer a helpful tool to monitor aggregation sites of this emblematic species in order to improve conservation efforts.